PENINGKATAN HASIL FERMENTASI BIOETANOL DARI NIRA SORGUM MANIS (Sorghum bicolor L. Moench) DENGAN MENGGUNAKAN BIAKAN CAMPURAN DUA GALUR KHAMIR - , Jasman ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Depletion of fossil energy and the need of eco-friendly energy endorse various efforts to obtain the new source and renewable energy, including bioethanol. The objective of this study was to increase ethanol yield from fermentation of sweet sorghum juice using mixed culture of yeast strains. The study was conducted in three steps: (1) selection of yeast strains used in the mixed culture, (2) application of mixed culture on fermentation of mixed sugar composed of sucrose, glucose, and fructose, and (3) application of mixed culture on fermentation of sweet sorghum juice. The first step was carried out by using each strain on fermenting glucose, fructose, sucrose, glucosefructose mixture, and sucrose-glucose-fructose mixture. The second step was performed by fermenting substrate of mixed sugar composed of sucrose, glucose, and fructose with 2:1:1 composition using the mixed culture of two selected strains. The last step was conducted by fermenting sweet sorghum juice using the mixed culture. There were two kind of sweet sorghum juice used in this study namely KCS105 and FS501. Ethanol produced during the study was analyzed using Conway, HPLC, and GC methods while residual sugars were analyzed using DNS and HPLC methods. The results showed that strains of OUT7921, OUT7913, and OUT7096 generally consumed sugar and produce ethanol more than the other strains. Therefore, these three strains were chosen to compose the mixed culture used in subsequent fermentation. Application of mixed culture on mixed sugar fermentation showed that mixed culture of OUT7913/OUT7921 gave the best of yield and ethanol concentration. Furthermore, the application of mixed culture on fermentation of sweet sorghum juice showed that OUT7913/OUT7921 culture was the best inoculum for KCS105 juice, while OUT7096/OUT7913 culture was the best for FS501 juice. Ethanol fermentation from sweet sorghum juice using mixed culture gave higher yield than that of using single culture, despite the fact that sweet sorghum varieties may also affect the yield. Key words: bioethanol, fermentation, mixed culture, yeast, sweet sorghum juice